Building a Common Future in Southern Africa - Mongardini, Joannes (International Monetary Fund, 2013)
The Southern African Customs Union (SACU) is the oldest customs union in the world, with significant opportunities ahead for creating higher economic growth and increased welfare benefits to the people of the region, by fulfilling its vision to become an economic community with a common market and monetary union. This volume describes policy options to address the barriers to equitable and sustainable development in the region and outlines a plan for deeper regional integration.